2000
DOI: 10.1046/j.1432-1327.2000.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized transcriptional gene expression of H+-ATP synthase subunits in different tissues of Fischer 344 rats of different ages

Abstract: Little is known about the relationship between the stoichiometry of polypeptides of multisubunit enzyme complexes and the absolute amount of each transcript of the complexes in mammalian tissues. Here we showed that the absolute amounts of the transcripts of most subunits of rat H 1 -ATP synthase examined greatly differed in the different tissues, showing the following hierarchy of tissue-specificity: heart . kidney . brain < liver. However, surprisingly, there was no difference in the expression pattern of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Considering sequence diversity in the predicted signal part of the c-F o -ATPase, it appears that the cloned cDNA of carp in the present study correspond to the P3 isoform of zebrafish c-F o -ATPase, which showed 96% identity in the amino acid sequence. Although P1 and P2 isoforms have been found in mammalian c-F o -ATPase (3,15,35) and Fugu genome database (Scaffold_1299 for P1 and Scaffold_6377 for P2), such isoforms could not be detected in carp fast muscle in this study. The fact that the mature c-F o -ATPase irrespective of isoforms were almost completely conserved among vertebrates including carp (see Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…Considering sequence diversity in the predicted signal part of the c-F o -ATPase, it appears that the cloned cDNA of carp in the present study correspond to the P3 isoform of zebrafish c-F o -ATPase, which showed 96% identity in the amino acid sequence. Although P1 and P2 isoforms have been found in mammalian c-F o -ATPase (3,15,35) and Fugu genome database (Scaffold_1299 for P1 and Scaffold_6377 for P2), such isoforms could not be detected in carp fast muscle in this study. The fact that the mature c-F o -ATPase irrespective of isoforms were almost completely conserved among vertebrates including carp (see Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…ATP synthase is a key enzyme in oxidative phosphorylation and responsible for the production of most of the ATP in mammalian organisms. The absolute amounts of the transcripts of most subunits of rat H + ‐ATP synthase examined differed greatly in different tissues, showing the following hierarchy of tissue specificity: heart > kidney > brain, liver 9 . We demonstrated here that one of the ATP synthase subunits is downregulated in senescent heart.…”
Section: Resultsmentioning
confidence: 65%
“…The absolute amounts of the transcripts of most subunits of rat H + -ATP synthase examined differed greatly in different tissues, showing the following hierarchy of tissue specificity: heart > kidney > brain, liver. 9 We demonstrated here that one of the ATP synthase subunits is downregulated in senescent heart. ATP synthase expression was reported to be decreased in the heart of those with chronic nicotine consumption, 10 while increased in the norepinephrine-infused hypertrophic heart.…”
Section: Verification Of the Differentially Expressed Genes In The Ramentioning
confidence: 65%